Ex vivo evaluation of retinal cytotoxicity after the use of multiple medical devices in pars plana vitrectomy in porcine eyes. (December 2021) - Gatto, Claudio; Romano, Mario R.; Giurgola, Laura; Ferrara, Mariantonia; Ragazzi, Eugenio; D'Amato Tothova, Jana
Abstract: This study aimed to evaluate viability of retinal cells after the use of multiple intraoperative devices, namely a vitreal dye (triamcinolone acetonide, TA), a ERM/ILM dye (solution of trypan blue 0.15% and brilliant blue 0.025%), and two intraocular tamponades, namely perfluoro-n-octane, (PFO) and silicone oil (SO 1000 cSt), with minimal and maximal removal of their residues, during a simulated pars plana vitrectomy (PPV) in porcine eyes ex-vivo. The in vitro cytotoxicity of each of these compounds was verified on ARPE-19 cells by direct tests according to the ISO 10993-5 (2009). Pars plana vitrectomy was performed on 25 enucleated porcine eyes divided in five groups according to the following conditions: Group A) No surgery control: eye bulbs were kept at room temperature for 40 min; Group B) Sham surgery: PPV with the sole use of BSS for 40 min; Group C) Cytotoxic control: PPV with BSS infusion (20 min) followed by intravitreal injection of 1H-PFO (contact time: 20 min); Group D) Surgery with residues: PPV with BSS infusion and sequential intravitreal injection of TA, ERM/ILM dye, PFO and SO, with minimal removal of each compound after a specified contact-time (overall duration: 40 min); Group E) Surgery with minimal residues: PPV performed as in group D, but with maximal removal of each compound (overall duration: 40 min). All the experimental procedures were performed at room temperature. Immediately after surgery, the retina was extracted from each eye bulb and samples of 3-mm diameter were prepared. Retinal viability was determined for each sample by 3-(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazolium bromide assay. A cell viability <70% was considered the cytotoxicity threshold. Kruskal-Wallis test was used to evaluate the differences in retinal viability between groups. No cytotoxicity was detected in retinal samples in groups A, B and E. Samples from eye bulbs that had undergone surgery with minimal removal of residues (group D) and cytotoxic controls (group C) showed high retinal cytotoxicity. The tested conditions indicated that the combined use of TA, ERM/ILM dye, PFO and SO during PPV does not affect retinal cells viability if all the devices are properly removed, whereas the cytotoxicity detected in group D may suggest that the presence and accumulation of the residues of the compounds used intraoperatively could negatively impact retinal viability due to a cumulative and/or synergistic cytotoxic effect between them, supporting the crucial role of an optimal removal of the intraoperative medical devices to ensure a safe vitrectomy to the patient. Highlights: Vitrectomy do not affect retinal viability if TA, blue dye, PFO and SO are well removed. Vitrectomy leaving residues of TA, blue dye, PFO, SO resulted in retinal cytotoxicity. The optimal removal of residues of medical devices is crucial to ensure a safe vitrectomy.